Mata Ortiz's dilemma: tourism, crafts and aesthetic enjoyment in the desert of Chihuahua, Mexico (Revista LIDER, 2020)
Tourism breaks contemporary scenes and it reconverts them into imaginaries that explain symbolic and political-economic strategies in the construction of local, regional and national identity. We propose the tourist as a re-colonizer in his role as an ad hoc consumer of the products created in response to his own demand. In the case studied, a village of Chihuahua reconverted as a tourist destination, sublies this process of reconquest of the spaces and places, a discourse, mediated by the saturation of the images and the imaginary regarding authenticity.